The evolution of APEC and its role in the Philippine trade and investment - Francis Mark A. Quimba; Mark Anthony A. Barral (Philippine Institute for Development Studies (PIDS), 2019)
This paper presents how APEC has evolved as an institution, the changes it undergoes and the challenges it has faced for the past decades. More importantly, this paper tries to enumerate the roles of APEC in positioning the Philippines in the global economy. Established in 1989 in Canberra, Australia, with twelve founding members, APEC desired to promote economic growth, foster and strengthen trade, and improve the living standards in the Region. Started as a simple program for sectoral and trade initiatives, APEC has come to achieve to become the largest are of free trade and investment by 2020. Forged and adopted in Bogor, Indonesia, in 1994, this challenge was known as the Bogor Goals, which aims to achieve long-term free and open trade not later than 2020; in particular, by 2010 for developed economies and by 2020 for developing economies. To ensure the achievement of Bogor Goals, three pillars were created as the main strategies of APEC. The first pillar is the Trade and Investment Liberalization. Through unilateral liberalization, APEC members voluntarily agree to liberalize a particular trade and investment area, including tariffs, non-tariff measures, services, investment, standards and conformance, customs procedures, and intellectual property rights, among others. This is done using the Individual Action Plans (IAPs), prepared by individual economy. The second pillar is Trade Facilitation, which eases and lessens the cost of doing business in the region by facilitating more efficient standards, customs, and other procedures relating to e-commerce, business travel, telecommunications, and government procurement, among others. The last pillar, the Economic and Technical Cooperation (ECOTECH), pertains to the collective actions of APEC to achieve its overall goals of attaining sustainable growth and improving economic and social well-being in the Region. [...]
Keywords: 330; APEC; globalization; Philippines; TILF; ECOTECH